Evaluation of Stability and Performance of Dam Foundations at Static State - Ghanizadeh, Ebrahim; Ghanizadeh, Mohammad (European Journal of Sustainable Development, 2017)
Dams possess high economic and political importance. They play critical role in agriculture, development of urban and rural areas, supplying drink water, generation of hydroelectric energy, control and regulation of water current velocity. Protection, retention and permanent evaluation of dam’s stability is major issue regarding high cost associated with dam construction and severity of consequences caused by dam instability. Since increased safety of dam is always accompanies with increased cost, it is necessary to ensure dam stability through designing, implanting and exploiting steps. Application of accurate instrument and behavior survey in engineering projects provides a permanent control over the execution trend and optimization of execution procedure in proportion to real status of stability. Thus it is vital to make suitable use of dam behavior survey and similar experiences to control dam’s stability and safety through designing, execution and exploitation phases. FLAC is a powerful multi-purpose software in geotechnical projects that is widely used to analyze dam stability based on finite difference method. The present study analyzes an embankment dam. By modeling of dam finite difference in the software and implementing earthquake scale, the effect of this earthquake on the dam is studied and suitable methods for dam and foundation stability were achieved. Stability causes hydrodynamic effects on the dam body and affects magnitude and distribution of static stresses as well. Keywords: static analysis, embankment dam, foundation, FLAC